A novel strategy for designing the antioxidant and adhesive bifunctional protein using the Lactobacillus strain-derived LPxTG motif structure. (April 2023) - Lu, Shuyi; Ou, Mingjuan; Ye, Qianwen; Tong, Xin; Guo, Yuxing; Pan, Daodong; Wu, Zhen
Abstract: Cell wall-anchored LPxTG proteins derived from the Lactobacillus are recognized to have excellent adhesion and gastrointestinal tolerance functions. Since the motif of LPxTG can interact with sortase A (SrtA) on the surface of Lactobacillus, it has great potential for various biotechnological applications. In this study, a bifunctional protein named LPxT-GYLEQ was designed by replacing the C-terminal hydrophobic domain with a synthetic antioxidant peptide containing an N-terminal glycine. It was found that the synthetic LPxT-GYLEQ protein exhibited better antioxidant activity in the H2 O2 -damaged HepG2 cells model. Meanwhile, it found that LPxT-GYLEQ protein can also exhibit good gastrointestinal tolerance function when pretreated with gastric juice and intestinal juice, and the DPPH radical scavenging ability of the LPxT-GYLEQ protein was increased by 12.8 % and 13.7 %, respectively, compared to the synthetic GYLEQ peptide. Further results also proved the good adhesion property of this synthetic protein (50 μg/mL) in the intestinal cell model. The novel strategy design of the antioxidative and adhesive bifunctional protein with the LPxTG motif structure offers a new idea for the protection of antioxidant peptides in the host oral delivery system. Graphical Abstract: A bifunctional protein named LPxT-GYLEQ with Rib domain has been designed by the replacement of the C-terminal hydrophobic domain of the surface LPxTG-motif proteins with a synthetic antioxidant peptide containing an N-terminal glycine, which possessed the better stabilizable antioxidant and adhesion activities. This novel strategy design of the antioxidative and adhesive bifunctional protein with the LPxTG-motif structure provides a new idea for the antioxidative peptides protection in the host oral delivery system. ga1 Highlights: A bifunctional protein with antioxidant and intestinal adhesion properties was developed. LPxT-GYLEQ protein possesses the ability of gastrointestinal tolerance and protection against antioxidant activity. LPxTG-motif structure provides a new idea for the protection of functional peptides in the oral delivery system.